PENGARUH PENGGUNAAN BINDER GELATINE DARI KULIT AYAMAYAM (Abalistes stellaris) UNTUK FINISHING KULIT KRAS CAKAR AYAM TERHADAP KETAHANAN GOSOK CAT TUTUP - Sri Sumarni (Politeknik ATK Yogyakarta, 2016)
His research aims to study the use of artificial gelatine binder abalistes stellaris leather, as a replacement for a patent binder for finishing tanned crust chicken scratch leather on the paint rub resistance. The material used is abalistes stellaris leather with neutralization treatment using a 5% citric acid, hydrochloric acid 5%, and 5% Acetic Acid. The use of binder abalistes stellaris leather for finishing on crust leather scribble with variations: 2%, 4%, 6%, 8% and 10% (b/b) compared to gelatine patent binder by using 3%. then tested rub resistance damp cloth and a dry cloth (SNI. 06-1996-1989). Data analysis used a randomized block design or RCBD where a block is a fabric paints wet rub resistance rub resistance versus paint dry cloth, with treatments 2%, 4%, 6%, 8%, 10% artificial gelatine from abalistes stellaris leather. The results of the research that the patent binder and artificial binder of abalistes stellaris leather showed significant difference. In terms, on the research the most excellent binder, made from abalistes stellaris leather that uses neutralizing acetic acid 5% with the use of binders 4% and 6% yield scrub resistance of paint damp cloth and a dry cloth is good when compared to using neutralizing with acid chloride 5% and 5% citric acid and patent binder.